Randomized trial of facilitated subcutaneous immunoglobulin in multifocal motor neuropathy. (31st May 2019) - Al‐Zuhairy, A.; Jakobsen, J.; Andersen, H.; Sindrup, S. H.; Markvardsen, L. K.
Abstract : Background and purpose: To optimize subcutaneous therapy with immunoglobulins, large volume infusion of immunoglobulin G facilitated by pretreatment with hyaluronidase (fSCIG) was compared to conventional infusion of multiple small dosages (cSCIG) in 20 patients with multifocal motor neuropathy. Methods: A randomized, non‐inferiority and observer‐blinded cross‐over design was applied with a treatment period of 24 weeks for each therapy. Results: In 18 patients fSCIG was feasible, two patients leaving the study due to side‐effects. The primary study variable, isometric strength, was unchanged, being 100.8% [95% confidence interval (CI) 94.8%–107.1%) in fSCIG and 105.9% (95% CI 99.8%–112.0%) in cSCIG. Secondary end‐points of disability, functions, impairments and quality of life showed no differences between the two treatments. Mild and short‐lasting generalized side‐effects were similar in the two groups, whereas the relative frequency of localized side‐effects at the injection site was increased after fSCIG [0.63 (95% CI 0.23–1.00) vs. 0.09 (95% CI 0.00–0.22), P = 0.005]. The preference of the patients favoured fSCIG for two out of five visual analogue scale scores as well as the total mean score of all preferences ( P = 0.03). Conclusions: Facilitated SCIG seems effective, feasible and safe. In addition, it is preferred by patients but is accompanied by a higher frequency of short‐lasting localized side‐effects.